Getting to root causes - Chrisinger, BW (Taylor and Francis, 2022)
Many planning and health collaborations name the built environment as an “upstream” factor for health disparities. Though some give mention to the structural dimensions of inequality (e.g., unequal distribution of income, discriminatory policies and practices), these are rarely the focus of planning–health study. Though this narrower approach is pragmatic, it restricts the policymaking discourse to potential built environment solutions that tend not to affect structural inequalities. I argue that equity planning can help focus research and practice on the root causes of unhealthy urban forms and unequal opportunities and engage directly with the challenging redistributional questions they require.